ASSESSMENT OF MEDICAL EXPOSURE IN PALLIATIVE THERAPY WITH SAMARIUM – 153 - Marina V. Li (Central Asian Journal of Medicine, 2022)
The scientific article is devoted to an actual problem - medical exposure. The aim of the study is to assessment the doses of irradiation of organs and tissues during palliative treatment patients with metastasized bone cancer. Over the past 20 years, only samarium-153 has been used for these purposes in Uzbekistan. Materials and methods. For the study, data from radioisotope laboratories of Tashkent medical institutions, where palliative treatment is carried out, were used. Radionuclide therapy with samarium-153, oxabiphor, was performed on 78 women who were diagnosed with mammary cancer, who had multiple bone metastases and pain syndrome. Equivalent doses of irradiation of the organs of patients were calculated by multiplying the introduced activity in MBq by the dose coefficients of the absorbed dose in mGy for specific organs per 1 MBq of activity. Results. Depending on the weight of the patients, dose loads on the bladder were in the range of 1.2–2.0 Gy; liver - 0.01 -0.02 Gy; kidneys - 0.6 - 1.0 Gy; small intestine - 0.01 - 0.02 Gy; the lower part of the large intestine - 0.02 - 0.03 Gy; upper colon - 0.01 - 0.02 Gy; ovaries - 0.02 - 0.03 Gy; whole body - 0.2 - 0.03 Gy. Conclusion. Due to the selective accumulation and manifestation of deterministic effects in the bone tissue, a decrease in pain in patients with metastasized bone lesions is clearly expressed. Equivalent radiation doses to other organs are below critical levels, so the risk of deterministic damage is minimal. The bladder experiences the greatest dose loads, then the kidneys, the lower part of the large intestine, the ovaries, small intestine, and the upper colon.